Medical Student Bridge Program Case: Mary Beth Chrispy - Ranna Nash; Danyelle Lee; Thomas Hunt (Association of American Medical Colleges, 2016)
Abstract Introduction Many colleges and medical schools are incorporating boot camps and transition programs for students prior to their first year of medical school. In these prematriculation programs, students are given early introductions to teaching modalities and study strategies. This resource provides a realistic case scenario that introduces students to the basic case format while guiding them through the thought process needed to work through a case. Additionally, it provides students with small-group skills that will be beneficial when working through cases in the first and second years of medical school. Methods The case features Mary Beth Chrispy, a 25-year-old second-year medical student who visits her primary care physician with complaints of fatigue and difficulty with focusing on her studies. Presenting questions throughout the case help guide students in making necessary connections and allow the facilitator to lead the students through each section of the case. There is no prereading to be done before the first meeting of the case. Students need to be willing to participate in the motions of the case so that they are prepared for their actual casework in the first year of medical school. Results Six questions pertaining to the case were placed on a self-assessment, and the students' ability to answer the questions, based on their work throughout the week, was measured. On five out of six questions, 94.4% of students (N = 19) answered correctly. On the remaining question, 100% of the students were able to answer correctly. We concluded that the activity met our learning objectives. Discussion Institutions that would like to include this case in their own prematriculation programs may want to utilize a standardized patient during its introductory clinical encounter.